Economic Essence of Agricultural Melioration and Scientific-Methodologic Aspects of Its Development - Sultanov, Bahodir (European Scientific Journal, ESJ, 2018)
Reclamation plays a major role in increasing the efficiency of the agricultural sector. Poor or lack of land reclamation might be the reason for less efficiency of the sector. This paper focuses on the theoretical framework of ameliorative, classification of ameliorative, and factors that affects sustainable development. Our findings show that the weather conditions, soil fertility, availability of sufficient water resources, and other factors have a major impact on crop yields, livestock productivity, labor costs, and product.